Stop Working and Start Living: or How to Squander Property and not Our Lives (KULT_online, 2014)
"Anti-work, Atheism, Adventure" are Federico Campagnia's antidotes to 'normative abstractions', that is ideological beliefs held dear both at the right and left side of the political spectrum. His passionate attack, aiming particularly at "the God of Work", faces us with a radical proposition: to stop living our lives as if there was some sort of heaven waiting for us (personal success, progress or a better world) and start living them as if it was our last night.